Measuring $$A_FB^b$$ A FB b and $$R_b$$ R b with exclusive b-hadron decays at the FCC-ee - Lars Röhrig; Kevin Kröninger; Romain Madar; Stéphane Monteil; Fabrizio Palla; Emmanuel Perez (European Physical Journal C: Particles and Fields)
Abstract This paper presents a novel tagging technique to measure the beauty-quark partial decay-width ratio $$R_b$$ R b and its forward–backward asymmetry $$A_{FB}^b$$ A FB b at the FCC-ee, using $$\mathcal {O}(10^{12})$$ O ( 10 12 ) Z-boson decays. The method is based on the exclusive reconstruction of a selected list of b-hadron decay modes in $$Z→ b\bar{b}$$ Z → b b ¯ events at the Z pole, which can provide the flavour and possibly the charge of the hemisphere. This approach effectively eliminates the contamination from light-quark physics events and reduces the leading systematic uncertainties arising from background contamination, tagging-efficiency correlations, and gluon-radiation corrections by exploiting the geometric and kinematic properties of beauty hadrons. This results in a total relative uncertainty of the order of 0.01 % for both observables. Furthermore, this precision allows to obtain a commensurate precision on the weak mixing angle $$\sin ^2(θ _\text {W}^{\text {eff}})$$ sin 2 ( θ W eff ) compared to the muon forward–backward asymmetry on the order of 0.002 %.